PENGARUH INDEPENDENSI, KOMPETENSI, MOTIVASI, OBJEKTIVITAS, INTEGRITAS, PENGALAMAN KERJA DAN ETIKA TERHADAP KUALITAS AUDIT APARAT INSPEKTORAT DALAM PENGAWASAN KEUANGAN DAERAH ( Studi Empiris pada Inspektorat Pemerintah Kota di Sumatera Barat) - Miftah Urrahmi; Muhammad Rasuli; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research aims to analyze and gets empirical prove of the influence of the independence, competence, motivation, objectivity, integrity, experience and ethics to the quality of audit result inspectorate apparatus in regional financial supervision. Respondents in this research is the auditors who work in the Office of the City Government Inspectorate in West Sumatra. The sampling is selected using purposive sampling, data collection method using a questionnaire with the number of auditors that the sample of this research was 61 auditors from 5 Office of the City Government Inspectorate in West Sumatra. This research is a quantitative model with data analysis methods include validity, reliability, normality test, classical assumptions: heteroscedasticity, multicollinearity, and test determinant coefficient and hypothesis test: t test using SPSS software version 20 to process data. The results of this research indicate that independence, competence, objectivity, experience and ethic have effect on the quality of audit result in p<0,05. While the motivation and integrity do not have effect on the quality of audit result in p>0,05. Based on the total adjusted R-square results proved that the variable independence, competence, motivation, objectivity, integrity, work experience, ethics affect the quality of audits of 0,868 or 86.8%. While the remaining 13.2% is explained by other variables that are not performed in this research.Keywords: independence, motivation, objectivity, integrity, and the quality of audit result